“Person in the barrel” syndrome: Unusual heralding presentation of squamous cell carcinoma of the lung - Verma, Rajesh (Ann Indian Acad Neurol, 2016)
Paraneoplastic neurological syndromes (PNS) are rare and relatively unusual in day to day clinical practice. Occasionally, PNS may be the heralding manifestation of the malignancy. Paraneoplastic syndromes are most commonly associated with small cell lung carcinoma and are rarely seen with non small cell lung carcinoma. In this case, we report a non-smoker, middle aged lady, who presented with “person in the barrel” syndrome due to myelo radiculoplexopathy as the first clinical manifestation of squamous cell carcinoma of the lung.